Antifibrotic drugs in lung transplantation and chronic lung allograft dysfunction: a review. (2nd June 2021) - Bos, Saskia; De Sadeleer, Laurens J.; Vanstapel, Arno; Beeckmans, Hanne; Sacreas, Annelore; Yserbyt, Jonas; Wuyts, Wim A.; Vos, Robin
This review aims to provide an overview of pre-transplant antifibrotic therapy on peri-transplant outcomes and to address the possible role of antifibrotics in lung transplant recipients with chronic lung allograft dysfunction. Lung transplantation is an established treatment modality for patients with various end-stage lung diseases, of which idiopathic pulmonary fibrosis and other progressive fibrosing interstitial lung diseases are growing indications. Theoretically, widespread use of antifibrotics prior to lung transplantation may increase the risk of bronchial anastomotic complications and impaired wound healing. Long-term graft and patient survival are still hampered by development of chronic lung allograft dysfunction, on which antifibrotics may have a beneficial impact. Antifibrotics until the moment of lung transplantation proved to be safe, without increasing peri-transplant complications. Currently, best practice is to continue antifibrotics until time of transplantation. In a large multicentre randomised trial, pirfenidone did not appear to have a beneficial effect on lung function decline in established bronchiolitis obliterans syndrome. The results of antifibrotic therapy in restrictive allograft syndrome are eagerly awaited, but nonrandomised data from small case reports/series are promising. Continuation of antifibrotic treatment during waiting time for lung transplantation proved to be safe. Pirfenidone did not appear to have a beneficial effect in bronchiolitis obliterans syndrome; results of antifibrotic therapy in RAS are eagerly awaited. https://bit.ly/3tgNbnq